In-situ growth of SiC nanostructures and their influence on anti-oxidation capability of C/SiC composites. (1st August 2017) - Dai, Jixiang; Sha, Jianjun; Shao, Junqi; Zu, Yufei; Lei, Mingkai; Flauder, Stefan; Langhof, Nico; Krenkel, Walter
Graphical abstract: Highlights: A catalyst free and simple method was developed to grow the SiC nanostructures. A dense cluster of SiC nanostructures was formed on the C/SiC composites in situ. Oxidation of C/SiC with nanostructures formed a silica layer. A silica layer provided an excellent anti-oxidation capability. Low viscosity layer favors the spreading and self-healing of silica in air flushing. Abstract: High purity SiC nanostructures were grown in situ on the surfaces of C/SiC composites by the chemical vapor reaction route to improve the anti-oxidation capability of C/SiC composites. It was found that the SiC nanostructures formed a dense cluster with a thickness of about 20 μm. The nanostructures mainly included nanoparticles and nanorods. The oxidation tests found that the SiC nanostructures could significantly improve the anti-oxidation capability of C/SiC composites, particularly, at the temperature beyond 900 °C. The improvement of the anti-oxidation capability of the C/SiC composites was attributed to the formation of a silica layer.